A toughened, crack-resistant and corrosion-resistant solid waste concrete and a preparation method thereof

By using all solid waste aggregates, natural aggregates, weak alkaline regulators and polycarboxylic acid water reducing agents in solid waste concrete, the problems of low early activity, easy cracking and poor dissolution resistance of solid waste concrete are solved, and the effects of toughening, cracking and dissolution resistance are achieved.

CN119661165BActive Publication Date: 2025-04-18SHIJIAZHUANG TIEDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510202417.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-18
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

During the use of solid waste concrete, there are problems such as low early activity, easy cracking, abnormal condensation, high energy consumption, poor toughness and poor dissolution resistance.

Method used

All solid waste aggregate and natural aggregate are used as aggregates, and weak alkaline regulators and polycarboxylic acid water reducing agents are added. Solid waste concrete that is toughened, crack-resistant and erosion-resistant through dry mixing, adding water, stirring, adding weak alkaline regulators and water reducing agents.

Benefits of technology

It improves the early and later hydration capacity of solid waste concrete, reduces shrinkage and cracks, enhances compactness and erosion resistance, and improves the crack resistance of solid waste concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661165B_ABST
    Figure CN119661165B_ABST
Patent Text Reader

Abstract

The present invention provides a toughened, crack-resistant and corrosion-resistant solid waste concrete and a preparation method thereof. Cement, fly ash, slag and natural aggregate are mixed; water, a weakly alkaline regulator and an admixture solution containing a polycarboxylic acid water reducer are successively added to obtain a concrete slurry; and the concrete slurry is obtained after curing. The present invention uses fly ash, slag solid waste and natural aggregate as aggregates, adds a water reducer to reduce the water consumption of concrete, improves the fluidity of concrete, and introduces a special weakly alkaline regulator particle, and utilizes its self-absorption and water-release behavior and "bridging" effect to enhance the early and late continuous hydration ability of the adhesive in the concrete, the effect of resisting autogenous shrinkage and drying shrinkage, improve the compactness and anti-corrosion performance of the concrete, and then improve the crack resistance of the all-solid waste concrete. The obtained test piece has no cracks on the surface, the 28d compressive strength reaches 46.6MPa, the 28d flexural strength reaches 8.5MPa, the autogenous shrinkage rate is 0.035%, and the drying shrinkage rate is 0.01%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cement-based building materials, and specifically relates to a toughened, crack-resistant and corrosion-resistant solid waste concrete and a preparation method thereof. Background Art

[0002] Solid waste concrete materials are made of solid waste-based cementitious materials supplemented with aggregates processed from tailings and waste rocks, and have excellent mixture properties, mechanical properties, long-term properties and durability. The main solid wastes used in solid waste concrete are steel slag, slag, desulfurized gypsum, fly ash, tailings sand and gravel, etc. In recent years, the research on the preparation of concrete using solid waste-based cementitious materials has made great progress. The solid waste-based cementitious system can be divided into multiple systems according to the type of solid waste added. Their chemical composition is similar, and different types of solid waste have different effects. Multiple solid wastes can be coordinated in composition, particle distribution, and excellent component reaction. This synergistic effect helps to improve the overall performance of concrete. From the current research results, the steel slag-slag-based system has low early activity and good durability; the steel slag-slag-desulfurized gypsum ternary system is relatively mature and widely used; other systems such as alkali-activated slag-fly ash, steel slag-slag-fly ash, etc. are also being gradually explored and improved.

[0003] There are some defects in the use of solid waste materials that should also be noted. For example, steel slag currently has three characteristics: (1) Steel slag is relatively hard. Due to its high hardness and low porosity, it is difficult to grind steel slag, resulting in an increase in overall costs. (2) Steel slag has poor stability. Steel slag contains a large amount of free calcium oxide and free magnesium oxide. These two substances are unstable at room temperature. The most direct manifestation is that they will appear in the finished concrete specimens. Bulging and other phenomena. (3) The cementitious properties of steel slag are low. Although the main components of steel slag are dicalcium silicate and tricalcium silicate, which are similar to cement, due to its own unique properties, it cannot achieve the same cementitious properties as cement.

[0004] Therefore, the main problems of concrete made of solid waste are: (1) Low early activity of concrete: After high temperature treatment, some solid waste materials will form a dense glass structure. This structure has high chemical stability, which makes it difficult to destroy and re-condense. Therefore, the early hydration activity is low, which reduces the early strength of concrete. (2) Concrete shrinks and is easy to crack: Solid waste materials have low activity and fast water evaporation, which affects the poor volume stability of concrete. (3) Abnormal coagulation: Certain components in solid waste may cause slow coagulation or accelerated coagulation of concrete, affecting construction performance. (4) Energy consumption problem: Solid waste materials such as steel slag have high hardness and poor abrasiveness, which leads to a certain increase in concrete construction costs and certain process limitations. (5) Poor toughness: The structural characteristics of solid waste materials themselves, low activity and fluctuations in chemical composition make the toughness of solid waste-based cementitious materials generally poor, which is also an important reason hindering the large-scale utilization of steel slag. (6) Poor corrosion resistance: The hydration activity and gelling properties of solid waste-based cementitious materials are inferior to those of cement. The early strength of hydration is low and it is easy to shrink. Microcracks are easily generated inside it. The hydrated calcium hydroxide, hydrated calcium silicate and other substances inside are easy to dissolve, and the external corrosive chloride, sulfate and other ions are easy to enter.

[0005] Therefore, in view of the above-mentioned shortcomings of solid waste concrete, the present invention takes chemical corrosion, which is the most difficult to control in the environment, as an example, and proposes a new technical solution for toughening and resisting chemical corrosion of solid waste concrete, so as to guide the durability and safety of solid waste concrete engineering structures. Summary of the invention

[0006] The object of the present invention is to provide a toughened, crack-resistant and corrosion-resistant solid waste concrete and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing toughened, crack-resistant and corrosion-resistant solid waste concrete, comprising the following steps:

[0009] (1) Dry mixing: Mix cement, fly ash, slag and natural aggregate evenly;

[0010] (2) After dry mixing, add water and continue stirring;

[0011] (3) Add a weak alkaline regulator and continue stirring to obtain a mixture;

[0012] (4) dissolving a polycarboxylate water-reducing agent in water to prepare an admixture solution, and adding the solution to the mixture of step (3), and continuing to stir to obtain a concrete slurry;

[0013] (5) Pour the concrete slurry into the mold and cure it;

[0014] Preferably, the preparation method of the weakly alkaline regulator is:

[0015] ① Add sodium acrylate, diethyl acrylate, polyvinyl alcohol and ammonium persulfate to deionized water and stir evenly;

[0016] ② Heat to carry out polymerization reaction, add polyethylene glycol, acetone and sucrose after the reaction, stir evenly and continue the reaction;

[0017] ③ After the reaction is completed, sodium hydroxide solution is added to adjust the pH of the reaction solution to a weak alkaline state;

[0018] ④ After adjusting the pH, the reaction solution is cooled to room temperature, and freeze-dried to terminate the polymerization reaction to obtain a block-shaped weak alkaline regulator; the block-shaped weak alkaline regulator is converted into a granular weak alkaline regulator, and its water content is adjusted;

[0019] ⑤ Use vacuum radio frequency heating to carry out pre-aging treatment.

[0020] Preferably, in step ① of the method for preparing the weak alkaline regulator, the mass ratio of sodium acrylate, diethyl acrylate, polyvinyl alcohol, ammonium persulfate and deionized water is (50-60): (5-10): (1-3): (0.1-0.5): 100;

[0021] Preferably, in step ② of the method for preparing the weak alkaline regulator, the mass ratio of polyethylene glycol, acetone, sucrose and deionized water is (0.01-0.04):(0.1-0.2):(0.1-0.5):100.

[0022] More preferably, in step ① of the method for preparing the weak alkaline regulator, the mass ratio of sodium acrylate, diethyl acrylate, polyvinyl alcohol, ammonium persulfate, and deionized water is 60:10:2:0.4:100;

[0023] More preferably, in step ② of the method for preparing the weak alkaline regulator, the mass ratio of polyethylene glycol, acetone, sucrose and deionized water is 0.02:0.2:0.3:100.

[0024] Preferably, in step ② of the preparation method of the weak alkaline regulator, the heating rate during heating is 20°C / min, the polymerization reaction temperature is 60-80°C, the reaction time after reaching the target temperature is 1-3h; the reaction time is 1-1.2h; the polyethylene glycol is polyethylene glycol 600;

[0025] Preferably, in step ③ of the method for preparing the weakly alkaline regulator, the mass concentration of the sodium hydroxide solution is 20-30%, and the pH of the reaction solution is adjusted to 8-10.

[0026] Preferably, in step ④ of the preparation method of the weak alkaline regulator, the freeze-drying temperature is -60°C to -40°C, the time is 1.5 to 2 hours, and the vacuum degree is 10 to 16 Pa; the particle size of the granular weak alkaline regulator is ≤ 180 μm; and the water content is 58 to 60%;

[0027] Preferably, in step ⑤ of the preparation method of the weak alkaline regulator, the temperature of vacuum radio frequency heating is 95° C., the frequency of radio frequency is 750-780 kHz, the pre-aging time is 12-14 h, and the water content of the weak alkaline regulator after treatment is 5-8%.

[0028] Preferably, in step (1), based on the total mass A of fly ash, slag and natural aggregate, the mass of fly ash is 30-50% of the total mass A; the mass of slag is 5-10% of the total mass A; the mass of natural aggregate is 40-50% of the total mass A; and the mass ratio of cement to the total mass A is (10-15):(90-85);

[0029] The cement is ordinary Portland cement with a P·O 42.5; the natural aggregate is crushed stone and sand; and the mixing time is 5-10 minutes.

[0030] Preferably, in step (1), the mixing mass ratio of cement, fly ash, slag and natural aggregate is 10:40:7:43; the mixing mass ratio of crushed stone and sand in the natural aggregate is 2:1; the particle size of the crushed stone is 5-20 mm, and the particle size of the sand is 0.75-4.75 mm;

[0031] Fly ash is Class I or Class II, with a specific surface area of ​​≥350m 2 / kg; slag is S95 or S105 grade slag, with a specific surface area of ​​≥400 m 2 / kg.

[0032] Preferably, in step (2), based on the total volume B of cement, fly ash, slag and natural aggregate, the mass volume ratio of the added water to the total volume B is 165kg:1m 3 ; The stirring time after adding water is 3~6min;

[0033] Preferably, in step (3), based on the total mass C of cement, fly ash, slag, natural aggregate and water, the mass of the weak alkaline regulator is 0.5-1% of the total mass C; and the stirring time is 5-10 min.

[0034] More preferably, in step (3), based on the total mass C of cement, fly ash, slag, natural aggregate and water, the mass of the weak alkaline regulator is 0.5% of the total mass C;

[0035] Preferably, in step (4), the mass ratio of polycarboxylate water-reducing agent to water is 1:5-1:8; the mass of the admixture solution added is 0.5-2% of the mass of cement; and the stirring time is 8-10 min;

[0036] Preferably, in step (5), after pouring into the mold, a vibrator is used to vibrate for 2 to 5 minutes; the curing temperature is 25±2°C, and the curing time is 28 days.

[0037] The invention provides toughened, crack-resistant and corrosion-resistant solid waste concrete, which is prepared by using the preparation method.

[0038] Beneficial effects:

[0039] The present invention uses all-solid waste aggregates (fly ash and slag) and natural aggregates as aggregates, adds a water reducer to reduce the water consumption of concrete and improve the fluidity of concrete, and introduces a special weak alkaline regulator particle, and utilizes its self-water release and toughening effects to prepare solid waste concrete, enhance the early and late continuous hydration ability of the solid waste adhesive in the concrete, and the effect of resisting autogenous shrinkage and drying shrinkage, improve the compactness and anti-corrosion performance of the concrete, and then improve the crack resistance of the all-solid waste concrete.

[0040] The weakly alkaline conditioning agent particles of the present invention have water absorption and water release properties, and can be used for concrete self-curing. In the early stage of concrete mixing, it can absorb excess free water, release water to supplement internal humidity during the concrete hardening process, and promote the continuous hydration of solid waste materials. Its alkalinity can also increase the gelation and hydration of solid waste, and finally reduce the shrinkage of concrete, and improve the crack resistance of concrete. Compared with the existing common particles with water absorption and water release properties, the weakly alkaline conditioning agent of the present invention has higher humidity sensitivity, can resist the dissolution of calcium hydroxide and ions in cement slurry, and actively release water one day after concrete molding to supplement the internal humidity of concrete, thereby enhancing the effect of resisting autogenous shrinkage and drying shrinkage.

[0041] The weakly alkaline regulator particles prepared by the present invention are well combined with the cement substrate and can also form a "bridge" overlapping effect, which can effectively release the stress of microcracks, reduce crack expansion, and further improve the crack resistance and corrosion resistance of all-solid waste concrete. Specifically, the weakly alkaline regulator particles are a kind of macromolecular substance, and the main chain and side chains of the molecule can better connect with the surface of inorganic particles such as fly ash and slag powder. Multiple molecular chains are directly entangled and overlapped to form a complex network structure, which can not only retain water and fix hydration products, but also promote hydration by contacting reactants with each other. The increase in the degree of hydration will reduce the porosity of the matrix, reduce the probability of dissolution of internal calcium hydroxide and hydrated calcium silicate, hydrated calcium aluminate and other hydration products, and reduce the probability of external corrosive ion penetration.

[0042] The addition of weak alkaline regulator particles of the present invention can cross-link with cement, fly ash, and slag, uniformly wet the surface of inorganic particles, help improve the curing effect inside the concrete, promote hydration, enhance density and toughness, stabilize the water absorption-release process, improve crack resistance, and adapt to complex environments. Among them, the "bridge" lap effect of the weak alkaline regulator particles and the constituent materials of the concrete enhances the deformation capacity of the concrete under stress, reduces the generation of cracks, and improves the toughness and crack resistance of the concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0044] Figure 1 This is a physical picture of a solid waste concrete specimen prepared by the preparation method of the present invention;

[0045] Figure 2 This is a SEM image of the solid waste concrete prepared in Example 1 of the present invention;

[0046] Figure 3 This is a SEM image of the solid waste concrete prepared in Example 1 of the present invention from another perspective;

[0047] Figure 4 The compressive strength and flexural strength curves of the solid waste concrete prepared in Examples 1 to 4 of the present invention;

[0048] Figure 5 The sulfate ion concentration curve at the same depth of the solid waste concrete prepared in Examples 1 to 4 of the present invention;

[0049] Figure 6 The compressive strength and flexural strength curves of the solid waste concrete prepared in Example 1 and Comparative Examples 1 to 3 of the present invention;

[0050] Figure 7 The sulfate ion concentration curve at the same depth of the solid waste concrete prepared in Example 1 and Comparative Examples 1 to 3 of the present invention is shown. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0052] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0053] In view of the existing problems, the present invention provides a method for preparing toughened, crack-resistant and corrosion-resistant solid waste concrete, comprising the following steps:

[0054] (1) Dry mixing: Mix cement, fly ash, slag and natural aggregate evenly;

[0055] (2) After dry mixing, add water and continue stirring;

[0056] (3) Add a weak alkaline regulator and continue stirring to obtain a mixture;

[0057] (4) dissolving a polycarboxylate water-reducing agent in water to prepare an admixture solution, and adding the solution to the mixture of step (3), and continuing to stir to obtain a concrete slurry;

[0058] (5) Pour the concrete slurry into the mold and cure it;

[0059] The preparation method of the weakly alkaline regulator is:

[0060] ① Add sodium acrylate, diethyl acrylate, polyvinyl alcohol and ammonium persulfate to deionized water and stir evenly;

[0061] ②Then heat to carry out polymerization reaction, add polyethylene glycol, acetone and sucrose after the reaction, stir evenly and continue the reaction;

[0062] ③ After the reaction is completed, sodium hydroxide solution is added to adjust the pH of the reaction solution to a weak alkaline state;

[0063] ④ After adjusting the pH, the reaction solution is cooled to room temperature, and freeze-dried to terminate the polymerization reaction to obtain a block-shaped weak alkaline regulator; the block-shaped weak alkaline regulator is converted into a granular weak alkaline regulator, and its water content is adjusted;

[0064] ⑤ Use vacuum radio frequency heating for pre-aging treatment, and obtain a weak alkaline regulator after the treatment.

[0065] Among them, the present invention uses diethyl acrylate as a small molecule cross-linking agent. The acrylate group thereof can react with the carboxyl and hydroxyl groups on the polymer chain to form a cross-linking structure. Ammonium persulfate is selected as an initiator for the organic reaction. The present invention uses the azeotrope of sodium acrylate, diethyl acrylate and polyvinyl alcohol as basic raw materials to prepare sodium polyacrylate. The water-swellable sodium polyacrylate belongs to a highly absorbent resin. After adding polyethylene glycol and acetone, it can catalyze the polymerization reaction and shorten the reaction time. At the same time, it can also increase the transparency of the prepared particles; and adding sucrose can increase the crystal content of the reactants, making the obtained particles more transparent.

[0066] In the step ①, sodium acrylate, diethyl acrylate, polyvinyl alcohol, and ammonium persulfate are all analytically pure; the mass ratio of sodium acrylate, diethyl acrylate, polyvinyl alcohol, ammonium persulfate, and deionized water is (50-60):(5-10):(1-3):(0.1-0.5):100;

[0067] More preferably, the mass ratio of sodium acrylate, diethyl acrylate, polyvinyl alcohol, ammonium persulfate, and deionized water is 60:10:2:0.4:100;

[0068] In the step ②, the heating rate during heating is 20°C / min, the polymerization reaction temperature is 60-80°C, the reaction time after reaching the target temperature is 1-3h; the reaction time is continued for 1-1.2h;

[0069] The polyethylene glycol is polyethylene glycol 600; the mass ratio of polyethylene glycol, acetone, sucrose and deionized water is (0.01-0.04):(0.1-0.2):(0.1-0.5):100;

[0070] More preferably, the mass ratio of polyethylene glycol, acetone, sucrose and deionized water is 0.02:0.2:0.3:100;

[0071] In the step ③, the mass concentration of the sodium hydroxide solution is 20-30%, and the pH of the reaction solution is adjusted to 8-10;

[0072] Among them, the pH value in this weakly alkaline range matches the hydration-promoting effect of the concrete cementitious composition, and is also a good condition for adjusting the particles to continuously release water, so as to improve the density and corrosion resistance of the concrete.

[0073] In step ④, the freeze-drying temperature is -60°C to -40°C, the time is 1.5 to 2 hours, and the vacuum degree is 10 to 16 Pa; the particle size of the granular weak alkaline regulator is ≤ 180 μm (passing through an 80-mesh sieve); the moisture content is 58 to 60%;

[0074] Among them, under this moisture content condition, the hydration inside the concrete can be effectively accelerated and the shrinkage of the concrete can be effectively alleviated, thereby improving its compaction ability.

[0075] In the step ⑤, the temperature of the vacuum radio frequency heating is 95° C., the frequency of the radio frequency is 750-780 kHz, the pre-aging time is 12-14 h, and the water content of the weak alkaline regulator after treatment is 5-8%.

[0076] In a preferred embodiment of the present invention, in step (1), the cement is PO 42.5 ordinary Portland cement; the natural aggregate is crushed stone and sand; the mixing time is 5 to 10 minutes to ensure that the components are evenly dispersed;

[0077] In a preferred embodiment of the present invention, in step (1), based on the total mass A of fly ash, slag and natural aggregate, the mass of fly ash is 30-50% of the total mass A; the mass of slag is 5-10% of the total mass A; the mass of natural aggregate is 40-50% of the total mass A; and the mass ratio of cement to the total mass A is (10-15):(90-85);

[0078] In a preferred embodiment of the present invention, in step (1), the mixing mass ratio of cement, fly ash, slag and natural aggregate is 10:40:7:43; the mixing mass ratio of crushed stone and sand in the natural aggregate is 2:1; the particle size of the crushed stone is 5-20 mm, and the particle size of the sand is 0.75-4.75 mm.

[0079] Fly ash is Class I or Class II, with a specific surface area of ​​≥350m 2 / kg; slag is S95 or S105 grade slag powder, with a specific surface area of ​​≥400 m 2 / kg.

[0080] In a preferred embodiment of the present invention, in step (2), based on the total volume B of cement, fly ash, slag and natural aggregate, the mass volume ratio of the added water to the total volume B is 165kg:1m 3 ; The stirring time after adding water is 3~6 minutes to achieve uniform workability.

[0081] In a preferred embodiment of the present invention, in step (3), the mass of the weak alkaline regulator is 0.5-1% of the total mass C of cement, fly ash, slag, natural aggregate and water.

[0082] More preferably, based on the total mass C of cement, fly ash, slag, natural aggregate and water, the mass of the weak alkaline regulator is 0.5% of the total mass C.

[0083] In a preferred embodiment of the present invention, in step (3), the stirring time is 5 to 10 minutes, so that the weak alkaline regulator is fully in contact with the above raw materials;

[0084] In a preferred embodiment of the present invention, in step (4), the mass ratio of polycarboxylate water-reducing agent to water is 1:5-1:8; the mass of the admixture solution added is 0.5-2% of the mass of cement; the stirring time is 8-10 min;

[0085] Among them, the addition of water reducing agent can further reduce the water consumption of concrete, improve the fluidity and strength of concrete, increase the internal density, and thus improve the overall durability.

[0086] In a preferred embodiment of the present invention, in step (5), after pouring into the mold, a vibrator is used to vibrate for 2 to 5 minutes; a method of covering with wet linen is used for curing to keep the surface of the concrete moist and promote cement hydration reaction; the curing temperature is 25±2°C and the curing time is 28 days;

[0087] The present invention also provides toughened, crack-resistant and corrosion-resistant solid waste concrete, which is prepared by the preparation method.

[0088] The following is a detailed description of the method for preparing toughened, crack-resistant and corrosion-resistant solid waste concrete according to the present invention through specific embodiments.

[0089] Example 1

[0090] This embodiment relates to a method for preparing toughened, crack-resistant and corrosion-resistant solid waste concrete, comprising the following steps:

[0091] (1) Dry mixing: Cement (P·O 42.5 ordinary Portland cement), fly ash, slag and natural aggregate were mixed for 10 min to ensure uniform dispersion of the components;

[0092] Among them, the natural aggregates are crushed stone and sand; the mixing mass ratio of cement, fly ash, slag and natural aggregate is 10:40:7:43; the mixing mass ratio of crushed stone and sand is 2:1;

[0093] The particle size of the crushed stone is 5-20mm, the particle size of the sand is 0.75-4.75mm, the fly ash is Class I ash, and the specific surface area is 436m 2 / kg, the slag is S105 grade slag, with a specific surface area of ​​589 m 2 / kg.

[0094] (2) After dry mixing, slowly add water and continue stirring for 5 minutes to achieve uniform workability; the mass volume ratio of the added water to the total volume B of cement, fly ash, slag and natural aggregate is 165kg:1m 3 .

[0095] (3) Add a weak alkaline regulator and continue stirring for 5 minutes to allow the weak alkaline regulator to fully contact with the above raw materials to obtain a mixture; wherein the mass of the weak alkaline regulator is 0.5% of the total mass C of cement, fly ash, slag, natural aggregate and water;

[0096] The preparation method of the weakly alkaline regulator is:

[0097] ① Add sodium acrylate, diethyl acrylate, polyvinyl alcohol, and ammonium persulfate to deionized water and stir evenly; wherein the mass ratio of sodium acrylate, diethyl acrylate, polyvinyl alcohol, ammonium persulfate, and deionized water is 60:10:2:0.4:100;

[0098] ② Then heat to carry out polymerization reaction, add polyethylene glycol 600, acetone and sucrose after the reaction, stir evenly and continue the reaction; wherein, the heating rate during heating is 20°C / min, the polymerization reaction temperature is 70°C, the reaction time after reaching the target temperature is 2h; the reaction time is continued for 1h; the mass ratio of polyethylene glycol 600, acetone, sucrose and deionized water is 0.02:0.2:0.3:100;

[0099] ③ After the reaction is completed, sodium hydroxide solution (mass concentration is 30%) is added to adjust the pH of the reaction solution to 8 (weakly alkaline);

[0100] ④ After adjusting the pH, the reaction solution was cooled to room temperature and freeze-dried (freeze-dried at -55°C for 2 hours and at a vacuum of 10 Pa) to terminate the polymerization reaction and obtain a block-shaped weak alkaline regulator; the block-shaped weak alkaline regulator was converted into a granular weak alkaline regulator (with a particle size of 180 μm) and its water content was adjusted to 60%;

[0101] ⑤ Use vacuum radio frequency heating for pre-aging treatment to obtain a weak alkaline regulator;

[0102] The temperature of vacuum radio frequency heating is 95° C., the frequency of radio frequency is 780 kHz, the pre-aging time is 12 h, and the water content of the weak alkaline regulator after treatment is 7%.

[0103] (4) dissolving the polycarboxylate water-reducing agent in water to prepare an admixture solution, and adding the solution to the mixture of step (3), and continuing to stir for 10 minutes to obtain a concrete slurry;

[0104] Among them, the mass ratio of polycarboxylate water-reducing agent to water is 1:5; the mass of the admixture solution added is 1% of the mass of cement.

[0105] (5) Pour the concrete slurry into the mold and vibrate it with a vibrator for 5 minutes. Cover the mold with wet linen for curing (the curing temperature is 25±2℃ and the curing time is 28 days) to keep the concrete surface moist and promote cement hydration reaction. After curing, the molded concrete is obtained.

[0106] Performance measurement: ① According to the determination method of sulfate ion percentage in hardened concrete specified in GB∕T 50476-2008 "Concrete Structure Durability Design Code", refer to GB / T11899-89 "Water Quality Sulfate Determination Gravimetric Method". The cured specimens were immersed in a sodium sulfate solution with a mass concentration of 5%, and the sulfate ion concentration in the concrete was measured, that is, the percentage of sulfate ions in the mass of the sample powder. The calculation method is:

[0107] w(SO4 2- )=m(SO4 2- mass) / m(powder sample mass)×100%

[0108] The specimen obtained in this example was immersed in a sulfate solution for 2 months and then sampled by drilling. The sulfate ion concentration was determined by precipitation method to be 1.18%. It can be seen that the specimen obtained by the method of the present invention has good corrosion resistance and performs well in the chemical corrosion resistance test, indicating that the specimen obtained by the method of the present invention is more resistant to corrosion in harsh environments.

[0109] Taking ordinary concrete (without the addition of fly ash, slag powder and weak alkaline regulator, that is, the mass proportion of cement in the cementitious material is 100%) as a control, the sulfate ion concentration of the ordinary concrete after immersion was measured to be 3.70%. By comparison, it can be seen that the corrosion resistance of the test piece obtained in this embodiment (cementitious material: cement, fly ash and slag, the mass proportion of cement in the cementitious material is 17.6%) is significantly improved.

[0110] ② According to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", after testing, the specimen obtained in this embodiment had a 28d compressive strength of 46.6MPa and a 28d flexural strength of 8.5MPa after 28d of curing, and there were no cracks on the surface of the specimen.

[0111] ③ According to JTG 3420-2020 "Test Procedures for Cement and Cement Concrete for Highway Engineering", the solid waste concrete prepared in this embodiment was measured to have a self-shrinkage rate of 0.035% and a drying shrinkage rate of 0.01%, which can meet the standards for self-shrinkage rate and drying shrinkage rate of ordinary concrete.

[0112] ④ The microscopic morphology of the concrete specimen obtained in this example was analyzed using a scanning electron microscope. The results are as follows: Figure 2 , Figure 3 shown.

[0113] Figure 1 The actual picture of the toughened, crack-resistant and corrosion-resistant solid waste concrete prepared according to the preparation method of the present invention. In order to further study the mechanism and effect of the weak alkaline regulator of the present invention, the microscopic morphology Figure 2 , Figure 3It can be seen that the hydration products such as CSH gel, calcium hydroxide, and calcium sulfonate are densely distributed, closely overlapped with each other, and the overall structure is dense. It can also be observed that many small particles are adhered to the matrix through the macromolecules of the weak alkaline regulator, filling the microcracks, resulting in fewer microcracks in the microstructure.

[0114] Example 2

[0115] This embodiment provides a method for preparing toughened, crack-resistant and corrosion-resistant solid waste concrete. Compared with Example 1, the difference is that the mass ratios of sodium acrylate, diethyl acrylate, polyvinyl alcohol, ammonium persulfate and deionized water in step ① of the weak alkaline regulator preparation method are different.

[0116] In this embodiment, the mass ratio of sodium acrylate, diethyl acrylate, polyvinyl alcohol, ammonium persulfate, and deionized water is 50:5:1:0.5:100; other steps and parameters are the same as those in Example 1.

[0117] The same performance measurement method as in Example 1 was used to immerse the specimen obtained in this example in a sulfate solution for 2 months and then drill a hole to take a sample. The sulfate ion concentration at the same depth was measured by a precipitation method and was 2.05%. The 28d compressive strength of the specimen obtained in this example was 40.5MPa, the 28d flexural strength was 7.5MPa, a small amount of fine cracks existed on the surface of the specimen, the autogenous shrinkage was 0.04%, and the drying shrinkage was 0.015%.

[0118] Example 3

[0119] This embodiment provides a method for preparing toughened, crack-resistant and corrosion-resistant solid waste concrete. Compared with Example 1, the difference is that the mass ratio of polyethylene glycol, acetone and sucrose in step ② of the weak alkaline regulator preparation method is different.

[0120] In this embodiment, the mass ratio of polyethylene glycol, acetone, sucrose and deionized water is 0.01:0.1:0.1:100; other steps and parameters are the same as those in Example 1.

[0121] The same performance measurement method as in Example 1 was used to immerse the specimen obtained in this example in a sulfate solution for 2 months and then drill a hole to take a sample. The sulfate ion concentration at the same depth was measured by a precipitation method and was 2.41%. The specimen obtained in this example had a 28d compressive strength of 39.8 MPa, a 28d flexural strength of 7.1 MPa, a small amount of fine cracks on the surface of the specimen, a self-shrinkage of 0.04%, and a drying shrinkage of 0.01%.

[0122] Example 4

[0123] This embodiment provides a method for preparing toughened, crack-resistant and corrosion-resistant solid waste concrete. Compared with Embodiment 1, the difference lies in that the amount of weak alkaline regulator added in step (3) is different.

[0124] In this embodiment, the mass of the weak alkaline regulator added is 1% of the total mass C, where the total mass C is the total mass of cement, fly ash, slag, natural aggregate and the water added in step (2); the other steps and parameters are the same as those in embodiment 1.

[0125] The same performance measurement method as in Example 1 was used to immerse the test piece obtained in this example in a sulfate solution for 2 months and then drill holes for sampling. The sulfate ion concentration at the same depth was measured by precipitation method and was 3.44%. The 28d compressive strength of the test piece obtained in this example was 38.3MPa, the 28d flexural strength was 6.9MPa, there were a few fine cracks on the surface of the test piece, the autogenous shrinkage was 0.045%, and the drying shrinkage was 0.01%. Due to the increase in the dosage, the water release amount increased exponentially, the water molecular weight wrapped on the surface of the cement particles was too much, and too many pores were formed inside the concrete, resulting in reduced strength.

[0126] Figure 4 This is a comparison chart of the 28d compressive strength and flexural strength of the solid waste concrete prepared in Example 1, Example 2, Example 3, and Example 4. Figure 5 The sulfate ion concentration at the same depth of the solid waste concrete prepared in Example 1, Example 2, Example 3, and Example 4. The difference between Examples 1 to 4 is that the raw material ratio in the preparation process of the weak alkaline regulator or the amount of the weak alkaline regulator used in the preparation process of the concrete is different, and the compressive and flexural strengths of Example 1 are the highest, and the measured sulfate ion content is the lowest, so the raw material ratio used in the preparation of the weak alkaline regulator and the amount of the weak alkaline regulator used are the optimal ratio and the optimal amount.

[0127] Comparative Example 1

[0128] This comparative example provides a method for preparing solid waste concrete. Compared with Example 1, the difference is that the pH of the reaction solution is adjusted differently in step ③ of the method for preparing a weak alkaline regulator.

[0129] In this comparative example, the pH of the reaction solution was adjusted to 7.1; other steps and parameters were the same as those in Example 1.

[0130] The same performance measurement method as in Example 1 was used to immerse the specimen obtained in this comparative example in a sulfate solution for 2 months and then drill a hole to take a sample. The sulfate ion concentration at the same depth was measured by a precipitation method and was 3.63%. The specimen obtained in this comparative example had a 28d compressive strength of 34.5MPa, a 28d flexural strength of 6.1MPa, a small amount of fine cracks on the surface of the specimen, a self-shrinkage of 0.05%, and a drying shrinkage of 0.02%.

[0131] Comparative Example 2

[0132] This comparative example provides a method for preparing solid waste concrete. Compared with Example 1, the difference is that the water content of the granular weak alkaline regulator in step ④ of the weak alkaline regulator preparation method is adjusted differently.

[0133] In this comparative example, the water content of the granular weak alkaline regulator is adjusted to 65%; other steps and parameters are the same as those in Example 1.

[0134] The same performance measurement method as in Example 1 was used to immerse the specimen obtained in this comparative example in a sulfate solution for 2 months and then drill holes for sampling. The sulfate ion concentration at the same depth was measured by precipitation method and was 4.07%. The 28d compressive strength of the specimen obtained in this comparative example was 32.4MPa, the 28d flexural strength was 5.7MPa, many fine cracks appeared on the surface of the specimen, the autogenous shrinkage was 0.06%, and the drying shrinkage was 0.03%. As the moisture content increases, the water released in the concrete increases, the degree of cement particle wetting increases, the water-cement ratio increases, and the pores increase after the concrete hardens, resulting in a decrease in strength.

[0135] Comparative Example 3

[0136] This comparative example provides a method for preparing solid waste concrete. Compared with Example 1, the difference is that no weak alkaline regulator is added in step (3) of this comparative example. The other steps and parameters are the same as those in Example 1.

[0137] The same performance measurement method as in Example 1 was used to immerse the specimen obtained in this comparative example in a sulfate solution for 2 months and then drill holes for sampling. The sulfate ion concentration at the same depth was measured by precipitation method to be 4.23% (because the mass proportion of cement in the cementitious material of this comparative example was 17.6% and it was not activated by alkali, the anti-corrosion performance of the specimen obtained in this comparative example was lower than that of ordinary concrete). The specimen obtained in this comparative example had a 28d compressive strength of 19.7MPa and a 28d flexural strength of 2.6MPa. There were a large number of fine cracks on the surface of the specimen, a self-shrinkage rate of 0.07%, and a drying shrinkage rate of 0.07%.

[0138] Figure 6 The figure is a comparison chart of the compressive strength and flexural strength of the solid waste concrete prepared in Example 1 and Comparative Examples 1 to 3. Figure 7It is the sulfate ion concentration at the same depth of the solid waste concrete prepared in Example 1 and Comparative Examples 1 to 3. Among them, some control parameters in the process of preparing the weak alkaline regulator in Comparative Example 1 and Comparative Example 2 exceed the range specified by the present invention. Comparative Example 1 does not control the weak alkalinity of the reaction solution, and the water content of the product prepared in Comparative Example 2 is higher than the specified range. The strength and corrosion resistance of the solid waste concrete prepared according to Comparative Example 1 and Comparative Example 2 are far inferior to those in Example 1. Therefore, the weak alkaline regulator and the preparation process parameters of the solid waste concrete proposed in the present invention can ensure that the performance of the preparation is the best. However, Comparative Example 3 did not use a weak alkaline regulator, and the performance of the prepared solid waste concrete was very poor, and the strength and corrosion resistance did not meet the standards for practical application. Therefore, the preparation of the weak alkaline regulator proposed in the present invention is the core to ensure the strength, toughness and corrosion resistance of the solid waste concrete.

[0139] In summary, the reagent concentration and the amount of weak alkaline regulator added when preparing the weak alkaline regulator in the present invention will affect the final performance of the concrete. The preparation and addition of the weak alkaline regulator can greatly improve the strength of the concrete. The pore structure present therein can effectively release the stress of microcracks, reduce crack expansion, and further improve the toughness and crack resistance of the solid waste concrete. At the same time, the self-absorption water characteristic of the weak alkaline regulator can effectively control the self-shrinkage and drying shrinkage of the cement during the early stage of coagulation and hardening. The late self-release water characteristic allows the solid waste-based cementitious materials and cement to continue to hydrate, continuously improve their strength, improve the internal pore structure, and reduce the proportion of connected open pores, thereby avoiding the internal hydration products from dissolving through the pores and the external corrosive ions from entering through the pores, thereby improving their anti-corrosion performance.

[0140] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing toughened, crack-resistant and corrosion-resistant solid waste concrete, characterized in that: The following steps are involved: (1) Dry mixing: Mix cement, fly ash, slag and natural aggregate evenly; (2) After dry mixing, add water and continue stirring; (3) Add a weak alkaline regulator and continue stirring to obtain a mixture; (4) dissolving a polycarboxylate water-reducing agent in water to prepare an admixture solution, and adding the solution to the mixture of step (3), and continuing to stir to obtain a concrete slurry; (5) Pour the concrete slurry into the mold and cure it; The preparation method of the weakly alkaline regulator is: ① Add sodium acrylate, diethyl acrylate, polyvinyl alcohol and ammonium persulfate to deionized water and stir evenly; ② Heat to carry out polymerization reaction, add polyethylene glycol, acetone and sucrose after the reaction, stir evenly and continue the reaction; ③ After the reaction is completed, add sodium hydroxide solution to adjust the pH of the reaction solution to a weak alkaline state; ④ After adjusting the pH, the reaction solution is cooled to room temperature, and freeze-dried to terminate the polymerization reaction to obtain a block-shaped weak alkaline regulator; the block-shaped weak alkaline regulator is converted into a granular weak alkaline regulator, and its water content is adjusted; ⑤ Use vacuum radio frequency heating to carry out pre-aging treatment.

2. The preparation method according to claim 1, characterized in that In step ① of the method for preparing the weak alkaline regulator, the mass ratio of sodium acrylate, diethyl acrylate, polyvinyl alcohol, ammonium persulfate and deionized water is (50-60): (5-10): (1-3): (0.1-0.5): 100; In step ② of the method for preparing the weak alkaline regulator, the mass ratio of polyethylene glycol, acetone, sucrose and deionized water is (0.01-0.04):(0.1-0.2):(0.1-0.5):

100.

3. The preparation method according to claim 2, characterized in that: In step ① of the preparation method of the weak alkaline regulator, the mass ratio of sodium acrylate, diethyl acrylate, polyvinyl alcohol, ammonium persulfate and deionized water is 60:10:2:0.4:100; In step ② of the method for preparing the weak alkaline regulator, the mass ratio of polyethylene glycol, acetone, sucrose and deionized water is 0.02:0.2:0.3:

100.

4. The preparation method according to claim 1, characterized in that: In step ② of the preparation method of the weak alkaline regulator, the heating rate during heating is 20°C / min, the polymerization reaction temperature is 60-80°C, the reaction time after reaching the target temperature is 1-3h; the reaction time is 1-1.2h; the polyethylene glycol is polyethylene glycol 600; In step ③ of the method for preparing the weak alkaline regulator, the mass concentration of the sodium hydroxide solution is 20-30%, and the pH of the reaction solution is adjusted to 8-10.

5. The preparation method according to claim 1, characterized in that: In step ④ of the preparation method of the weak alkaline regulator, the freeze-drying temperature is -60°C to -40°C, the time is 1.5 to 2 hours, and the vacuum degree is 10 to 16 Pa; the particle size of the granular weak alkaline regulator is ≤ 180 μm; and the water content is 58 to 60%; In step ⑤ of the preparation method of the weak alkaline regulator, the temperature of vacuum radio frequency heating is 95° C., the frequency of radio frequency is 750-780 kHz, the pre-aging time is 12-14 h, and the water content of the weak alkaline regulator after treatment is 5-8%.

6. The preparation method according to claim 1, characterized in that: In step (1), based on the total mass A of fly ash, slag and natural aggregate, the mass of fly ash is 30-50% of the total mass A; the mass of slag is 5-10% of the total mass A; the mass of natural aggregate is 40-50% of the total mass A; and the mass ratio of cement to the total mass A is (10-15):(90-85); The cement is ordinary Portland cement with a P·O 42.5; the natural aggregate is crushed stone and sand; and the mixing time is 5-10 minutes.

7. The preparation method according to claim 6, characterized in that: In step (1), the mixing mass ratio of cement, fly ash, slag and natural aggregate is 10:40:7:43; the mixing mass ratio of crushed stone and sand in the natural aggregate is 2:1; the particle size of the crushed stone is 5-20 mm, and the particle size of the sand is 0.75-4.75 mm; Fly ash is Class I or Class II, with a specific surface area of ​​≥350m 2 / kg; slag is S95 or S105 grade slag, with a specific surface area of ​​≥400 m 2 / kg.

8. The preparation method according to claim 1, characterized in that: In step (2), based on the total volume B of cement, fly ash, slag and natural aggregate, the mass volume ratio of the added water to the total volume B is 165kg:1m 3 ; The stirring time after adding water is 3~6min; In step (3), based on the total mass C of cement, fly ash, slag, natural aggregate and water, the mass of the weak alkaline regulator is 0.5-1% of the total mass C; and the stirring time is 5-10 min.

9. The preparation method according to claim 8, characterized in that: In step (3), based on the total mass C of cement, fly ash, slag, natural aggregate and water, the mass of the weak alkaline regulator is 0.5% of the total mass C; In step (4), the mass ratio of polycarboxylate water-reducing agent to water is 1:5-1:8; the mass of the admixture solution added is 0.5-2% of the mass of cement; the stirring time is 8-10 min; In step (5), after pouring into the mold, vibrate with a vibrator for 2 to 5 minutes; the curing temperature is 25±2°C, and the curing time is 28 days.

10. A toughened, crack-resistant and corrosion-resistant solid waste concrete, characterized in that: The solid waste concrete is prepared using the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Super absorbent resin with high absorbent velocity and preparation method

    CN103360555A

  • Novelmultifunctional ready-to-useaerogel composite for whole blood component protection and preparation method of novelmultifunctional ready-to-useaerogel composite

    CN106832439A